Self-reported foot pain with plantar fasciitis symptoms among dental practitioners registered with the Manila Dental Chapter 3rd quarter scientific seminar - Layugan, Kim Clemens B.
Dental practitioners are at high risk for developing various musculoskeletal disorders due to the physical demands of their profession. Due to prolonged static or standing position, dentist may be risk of having plantar fasciitis. Plantar fasciitis is an inflammation of the plantar fascia and is also considered one of the most common foot conditions as stated by Mcpoil et al. (2008). The study aimed to document the occurrence of foot pain with plantar symptoms among local dentists. METHODS: The study was descriptive cross sectional and the investigators used complete enumeration. The total number of attendees for the 3rd Quarter Scientific Seminar of MDC was 81. RESULTS: This study revealed that foot pain is commonly occurring among the dentist-participants of MDC 3rd Scientific Seminar (76%) with plantar fasciitis-like symptoms appearing in 32% of those who had foot pain. Plantar fasciitis equally occurred among younger adults and older adults. There were more female participants in the study and was reflected in the higher occurrence of plantar fasciitis among females (75%). The proportion of pre-obese and obese participants reporting plantar fasciitis-like symptoms (50%) is higher compared to those without plantar fasciitis-like symptoms. Occurrence of plantar fasciitis-like symptoms increases with increased hours and days of work and years of practice, and alternating positions while doing dental procedures. Plantar fasciitis was seen in a substantial number among those who did not engage in prolonged activities. The proportion of plantar fasciitis-like symptoms is higher in the foot-controlling foot(88%) as compared to the non-foot. Flat shoes are commonly used during treatment and revealed a higher occurrence of plantar fasciitis-like symptoms (94%). CONCLUSION: There is high occurrence of foot pain among dental practitioners, 76%. The occurrence of foot pain with plantar fasciitis symptoms among dentists who experienced foot pain is 16 out pf 50 or 34%.